2016
DOI: 10.5812/iranjradiol.24014
|View full text |Cite
|
Sign up to set email alerts
|

Changes of T2 Relaxation Time From Neoadjuvant Chemotherapy in Breast Cancer Lesions

Abstract: BackgroundNeoadjuvant chemotherapy (NAC) is generally an effective method of reducing locally advanced malignant breast lesions before surgery; assessing the tumor response to NAC is crucial for patient management. T2 relaxation times can reflect biological state of lesions, may prove useful to assess the response to NAC.ObjectivesTo investigate the lesion T2 relaxation times change in breast cancer neoadjuvant chemotherapy (NAC).Patients and MethodsIn total, 26 patients underwent NAC. Magnetic resonance imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…Previous studies on breast relaxometry have observed significant differences in T 1 and T 2 relaxation times between normal fibroglandular breast tissue and benign and malignant breast tumors . Changes in T 2 relaxation time has also been used to characterize response to chemotherapy in breast cancers . However, the T 1 and T 2 values reported for normal breast tissue show a wide variation due to the differences in mapping techniques and field strengths .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on breast relaxometry have observed significant differences in T 1 and T 2 relaxation times between normal fibroglandular breast tissue and benign and malignant breast tumors . Changes in T 2 relaxation time has also been used to characterize response to chemotherapy in breast cancers . However, the T 1 and T 2 values reported for normal breast tissue show a wide variation due to the differences in mapping techniques and field strengths .…”
mentioning
confidence: 99%
“…However, the T 1 and T 2 values reported for normal breast tissue show a wide variation due to the differences in mapping techniques and field strengths . Similarly, studies on response assessment to treatment used different T 2 mapping techniques, which affects comparability of these results . For quantitative imaging techniques to be successfully used in practice, assessment of measurement variability and repeatability are crucial to interpret results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An additional multi‐TE acquisition to measure the T 2 of water can be implemented with a scan time of less than a minute, and is recommended to improve the accuracy of metabolite quantification. This may be particularly pertinent if using quantitative MRS to assess treatment response, as tumor water T 2 is known to reduce following treatment . However, if water T 2 values for individual cases are not available, then the mean values for the relevant tissue type would be preferable to default values.…”
Section: Discussionmentioning
confidence: 99%
“…This may be particularly pertinent if using quantitative MRS to assess treatment response, as tumor water T 2 is known to reduce following treatment. [27][28][29] However, if water T 2 values for individual cases are not available, then the mean values for the relevant tissue type would be preferable to default values.…”
Section: Discussionmentioning
confidence: 99%